SOCIAL JUSTICE AND REPRESENTATION OF SOCIO-ECONOMIC GROUPS IN STUDY PROGRAMS OF DIFFERENT PRESTIGE IN LITHUANIA - Lazutka, Romas; Šliužaitė, Dovilė (Acta Paedagogica Vilnensia, 2012)
In this article, access to higher education is presented from several perspectives of social justice. It is shown that the Lithuanian higher education policy is based on the utilitarian and meritocratic principles noted in the Constitution of the Republic of Lithuania. As higher education becomes universal, the researchers should differentiate between research of social justice at different prestige universities and study programs. The results of a survey in which students of two Lithuanian universities were questioned show that young people from the lower economic and educational layers are less represented in the most prestigious study programs in Lithuania and more often study in low-prestige study programs. The state provides financial support to students (in the form of study vouchers and scholarships) depending on their academic achievements. That is why children from wealthier families more often receive this support. The survey has also revealed that the well-being of students who are studying in the most popular and prestigious study programs is much higher than of their colleagues who are less successful in the academic aspect. The living conditions, income and the need to work during their studies are very different between those two groups of students. It may seem paradoxical that the students’ division by the prestigious and low-prestige study programs on the socio-economic background and the state-provided financial assistance which depends on the academic achievements of students themselves are not considered negative. A large number of students face the problem of evaluating the higher education system in terms of social justice, while the devotion criteria of study vouchers and scholarships are considered to be fair.